On some problems of the concept of media literacy - Žarić, Dragana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
The paper points out the challenges and problems faced by media literacy as an educational and generally public strategic concept, with a focus on the use of the term itself and certain terminological ambiguities, then on reductionist practices in the implementation of media literacy training, and the political and ideological instrumentalization of the idea. The challenge before media literacy is the reality determined by technological development and the tendency to quantify, schematize and automate media literacy skills so that they take on computer logic, without being grounded in critical thinking.
Keywords: media literacy, media education, critical thinking, ideology, technology